Regulasi, Implementasi Ritel Modern, dan Tradisional Perspektif Maqashid Al-Syari’ah - Ezwin Fahrurrozi; Mohammad Saleh (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2022)
The phenomenon of the gap between traditional markets, UMKM, and cooperatives with modern retailers was the attitude of rejection of some groups of people both with demonstrations and so forth. This research was conducted to answer the problem formulation: (1) How was the Regulation and Implementation of Traditional Markets in the Maqashid Al-Shari'ah Perspective ?, (2) What was the Regulation and Implementation of Modern Retail in the Maqashid Al-Syari'ah Perspective?The method used in this research was qualitative research with descriptive research type. Data collection techniques were interviews, observation, and documentation which blessed the formulation of the problem. The regulation and implementation of traditional markets in the view of Maqashid Al-Shari'ah can be classified into three categories. Dharuriyat, Hajiyat, Tahsiniyat. While the implementation of the regulation was not fully applicable, most of it can be applied. such as providing a parking area and a lack of keeping the place clean. While the regulation of modern retail in the view of Maqashid Al-shari'ah was classified into three categories as well. Dharuriyat, Hajiyat, Tahsiniyat. While the implementation of the regulation was still not fully realized, for example, the distance separating modern retail and traditional markets and some that did not have licenses.